Motivasi Anggota KWT Madu Mulyo dalam Kegiatan Pengolahan Pangan di Kelurahan Pulisen Kecamatan Boyolali Kabupaten Boyolali - Wiratri, Arsita Dyah; Suwarto, Suwarto; Setyowati, Retno (Universitas Muhammadiyah Semarang, 2023)
According to the Decree of the Minister of Agriculture No.484 of 2021, so far agricultural development has only focused on the upstream sector. There is a need for industrialization based on the processing of agricultural, forestry, fishery, and non-agro commodities that are integrated upstream and downstream. According to the results of the 2018 Inter-Census Agricultural Survey, the percentage of food processing activities by farmers at the national level and Central Java Province is still very low. There is only one KWT in Boyolali Subdistrict that consistently conducts food processing until now, namely KWT Madu Mulyo located in Madumulyo Hamlet, Pulisen Village, Boyolali Subdistrict, Boyolali Regency. This study aims to analyze the level of motivation of KWT Madu Mulyo members in food processing activities, determine the factors that form the motivation of KWT members, and determine the relationship between the forming factors and the motivation of KWT Madu Mulyo members in food processing activities. This research method is quantitative method. The results showed that the level of motivation of KWT Madu Mulyo members in food processing as a whole is high which includes motivation based on existence needs is high, motivation based on relatedness needs is very high, and motivation based on growth needs is low. Factors shaping motivation are divided into internal and external factors. Internal factors include cosmopolitanity, respondents' income, number of children under five years old.